Особливості інваріантної міри дивного атрактора математичної моделі бактерії - Grytsay, V. (Publishing house "Academperiodika", 2022)
The bacteria metabolic process of open nonlinear dissipative system far from equilibrium point is modeled using classical methods of synergetics. The invariant measure and its convergence in the phase space of the system was obtained in strange attractor mode. The distribution of point density of trajectory intersection of phase space cells with maximum invariant measure and convergence in time of its average value was obtained. The result concluded is that the value of an invariant measure can be a characteristic of the transitional process of adaptation of cell metabolic process to change outside environment.